Regional differences in NREM sleep slow-wave activity in mice with congenital callosal dysgenesis. - Vyazovskiy, V; Tobler, I (2005)
Topographic differences in the sleep EEG have been repeatedly found in humans and rodents. A frontal predominance of EEG slow-wave activity (0.75-4 Hz; delta band) during non-rapid eye movement (NREM) sleep is particularly evident under conditions of increased sleep propensity. Local aspects of neuronal connectivity in the neocortex that are modified by specific neuronal stimulation may underlie these differences. To investigate the role of altered neuronal connectivity on anterior-posterior EEG topography, sleep was recorded in mice with congenital dysgenesis of the corpus callosum (B1 strain) during baseline and after 6 h sleep deprivation (SD). In these mice neuronal connections within a hemisphere are increased due to the longitudinal Probst bundle, a structure of re-routed callosal fibers. After SD the frequencies above 1.5 Hz within the delta band in NREM sleep were reduced in B1 mice compared with control C57BL/6 mice, a strain that has a normal corpus callosum, while power in the lowest frequency band (0.75-1.0 Hz) was enhanced in B1 mice. The differences between the strains subsided in the course of recovery. The redistribution of EEG power within the delta band in the frontal region in mice with a well developed Probst bundle, suggests a role of intracortical connectivity in local sleep regulation.